ANALISIS KETERKAITAN PENDAPATAN DENGAN MUTU BOKAR YANG DIHASILKAN PETANI KARET RAKYAT DI PROVINSI JAMBI - Napitupulu, Dompak; Efran, Endy (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2018)
ome research showed that the quality of natural rubber produced by smallholder in Jambi Province is getting worst, while the international rubber market on the other hand needs higher quality. This research is aimed to find out whether the natural rubber price received by farmer is linked to the rubber quality marketed in Jambi Province. The research was undertaken in four regency main rubber producing samples. Data was both primary and secondary data. The research found that the natural rubber was marketed in monopolistic manner, in which the natural rubber price was mainly controlled by trader. Majority (81,33 %) smallholder farmer sold their natural rubber to certain local trader. The natural rubber quality was range from low (50.09 %) to medium (76,14 %) grade, with the average grade was 62,27 %. Furthermore, the research was also showed that the price ranges from Rp. 5000/Kg to Rp. 10.800/Kg and the average price was Rp. 7.499,02/Kg. The research was also found that there is a weak correlation between price paid to the farmer and the natural rubber quality sold by the farmer in Jambi Province.